Efficacy of Symmetrical and Asymmetrical Pushed Negotiations in Boosting Speaking - Parviz Ghasedi (Journal of English Language Pedagogy and Practice, 2019)
This study was set out to shed light on the efficacy of pushed output directed by scaffolding on 41 (24 female and 17 male) upper-intermediate EFL learners’ speaking fluency and accuracy. A public version of IELTS speaking test was held to measure learners’ entrance behavior. Then, they were randomly assigned into symmetrical, asymmetrical, and control group. The experimental and control groups covered 7 lessons of New Interchange 2 during 15 sessions, twice a week for about 45 minutes each session. Control group received placebo while symmetrical and asymmetrical groups worked on pushed output tasks. The data were audio recorded and transcribed for statistical analyses. The results indicated the efficacy of pushed output in boosting speaking. However, tests of between-subjects effects revealed that the mean score of the control group was not significantly different from that of experimental groups concerning speaking fluency. Furthermore, the results of Tukey's HSD post-hoc tests showed that asymmetrically pushed output activities were more effective in enhancing learners speaking accuracy. In sum, the results suggested that the implementation of pushed out put strategies in student centered contexts could be considered as an effective way in the development of learners’ oral output.